Anxiety and Depression as Longitudinal Predictors of Mild Cognitive Impairment in Older Adults. (May 2017) - Freire, Antônio Carlos Cruz; Pondé, Milena Pereira; Liu, Aihua; Caron, Jean
Introduction: Few studies have dealt with the potential correlation between anxiety, depression, and cognitive impairment in community-dwelling older adults. Method: This longitudinal study was conducted in the city of Montreal, Canada, with 352 older adults aged 55 years or more. The participants were interviewed at baseline and again 2 years later. The Montreal Cognitive Assessment (MoCA) score was estimated and compared between the 2 time points, the Composite International Diagnostic Interview (CIDI) was used to assess major depression and anxiety, and the K10 measured high psychological distress. Likewise, major depression, anxiety disorders, and psychological distress were evaluated at the 2 study time points. Results: In older adults with a diagnosis of depression or anxiety at baseline, no significant reduction in the MoCA score indicating deterioration in cognitive function was found 2 years later. Nevertheless, in individuals with a high level of psychological distress at baseline, there was a significant reduction in MoCA scores 2 years later, indicating deterioration in cognition. The findings of the present study suggest that a high level of psychological distress in addition to environmental factors may constitute important predictors for cognitive health.